Catalytic hydrazine disproportionation mediated by a thiolate-bridged VFe complex. Issue 37 (17th April 2019) - Gu, Nina X.; Ung, Gaël; Peters, Jonas C.
Abstract : A heterobimetallic VFe complex is demonstrated to catalyse hydrazine disproportionation with yields of up to 1073 equivalents of NH3 per catalyst, comparable to the highest turnover known for any molecular catalyst. Abstract : A heterobimetallic VFe complex is demonstrated to catalyse hydrazine disproportionation with yields of up to 1073 equivalents of NH3 per catalyst, comparable to the highest turnover known for any molecular catalyst. Notably, the heterobimetallic complex is appreciably more active than monometallic analogues of the V and Fe sites, suggesting that bimetallic cooperativity may facilitate the observed catalysis.